HUBUNGAN STATUS GIZI , ANEMIA, DAN RIWAYAT ABORTUS DENGAN KEJADIAN ABORTUS - Desmansyah, Desmansyah; Oktavianis, Erita; Ompu P, Syerly (JOURNAL OF HEALTH SCIENCE, 2021)
Abortion is the termination of pregnancy before the 20th week (calculated from the first day of the last menstrual period). Another definition states that abortion is the expulsion of products of conception weighing <500 grams. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all pregnant women totaling 2110 pregnant women. The sample of this research used random sampling method. The sample of this study amounted to 95 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis found that there was a relationship between nutritional status (p value = 0.006), there was a relationship between anemia (p value = 0.000), and there was a relationship between abortion (p value = 0.000) and the incidence of abortion. The suggestions are expected for health workers so that this research can be taken into consideration in decision making, can improve the quality of services and especially regarding the incidence of abortion. Keywords: nutritional status, anemia, and abortion